Relação entre poluição atmosférica e doenças respiratórias em crianças de 0 a 5 anos na Paraíba : contribuição na tomada de decisões de políticas públicas voltadas ao controle da poluição do ar. - Egypto, Ilana Andrade Santos do (2017)
INTRODUCTION: Most of Brazilian States has no network of air quality monitoring, but all are exposed to air pollution from industries, automobiles, fires and those produced naturally by the environment. In the State of Paraíba no monitoring of air quality and therefore, there is no measurement of atmospheric pollutants and climatic variables. OBJECTIVE: Assess the relationship between air pollution and hospital admissions of children under five by respiratory diseases in Paraíba: contribution in decision-making of public policies aimed at controlling air pollution. METHODOLOGY: Analytical and descriptive study of the spatial distribution of vulnerable areas in relation to socioeconomic data, data on health information (hospitalization), population and pollutant sources (fleet and burned). The tabs and data analyses were conducted for the State of Paraíba stratified by region. We opted for the use of thematic cartography for the generation of maps of vulnerability to consider its potential as a tool for easy and intuitive visualization, to communicate the results of the environmental risk assessments. Descriptive analysis, Chi-square test, Kruskal-Wallis, and multiple comparisons of Dunn. The significance level was 5%. RESULTS: There is no relationship between the increase of air pollution and hospital admissions of children from zero to five years for respiratory problems. With respect to the spatial distribution of the hotspots and hospitalization, we have that in 2010 was the worst year among the analyzed in this study. The regions with the largest numbers of cases are the hinterland and coast. CONCLUSION: There is a need for a balance between economic development and sustainability. A plan of strategies should be designed and implemented, not depending on only one institution and the set of actions of various organs for the results to be favourable both to the quality of life of the population as to the economy of the State.